Driver gene combinations dictate cutaneous squamous cell carcinoma disease continuum progression - Bailey, Peter; Ridgway, Rachel A.; Cammareri, Patrizia; Treanor-Taylor, Mairi; Bailey, Ulla-Maja; Schoenherr, Christina; Bone, Max; Schreyer, Daniel; Purdie, Karin; Thomson, Jason; Rickaby, William; Jackstadt, René-Filip; et al. (Nature Communications, 2023)
The molecular basis of disease progression from UV-induced precancerous actinic keratosis (AK) to malignant invasive cutaneous squamous cell carcinoma (cSCC) and potentially lethal metastatic disease remains unclear. DNA sequencing studies have revealed a massive mutational burden but have yet to illuminate mechanisms of disease progression. Here we perform RNAseq transcriptomic profiling of 110 patient samples representing normal sun-exposed skin, AK, primary and metastatic cSCC and reveal a disease continuum from a differentiated to a progenitor-like state. This is accompanied by the orchestrated suppression of master regulators of epidermal differentiation, dynamic modulation of the epidermal differentiation complex, remodelling of the immune landscape and an increase in the preponderance of tumour specific keratinocytes. Comparative systems analysis of human cSCC coupled with the generation of genetically engineered murine models reveal that combinatorial sequential inactivation of the tumour suppressor genes Tgfbr2, Trp53, and Notch1 coupled with activation of Ras signalling progressively drives cSCC progression along a differentiated to progenitor axis. Taken together we provide a comprehensive map of the cSCC disease continuum and reveal potentially actionable events that promote and accompany disease progression.
Gesehen am 17.11.2023